The Effectiveness of Training Candidates for Heads of School Libraries by Public Library - Fitria Okta Khairunnisyah; Fransiska Timoria Samosir; Aang Gunaidi (Record and Library Journal, 2023)
Background of the study: In addition to helping school administrators maximize the function and role of the school library as a medium of learning for teachers and students, the head of the school library is also a school teacher who has received education and training in the field of libraries. Purpose: Measuring the Effectiveness of the Implementation of Training for Candidates for Heads of School Libraries in Bengkulu Province Method: The method used in this study is a descriptive method with a qualitative approach. The data technique used is Interactive Analysis (Interactive Model of Analysis), namely by describing and describing information from each component part that is assessed. Findings: The results of the study show that the implementation of the training for prospective school library principals has been effective. It is shown in the results that the training participants for prospective school librarian can improve the skills of library managers in managing school libraries, improve library management standards, and apply library automation technology that can be said to be effective. Conclusion: The implementation of the Library Head Training and Education in this study has been quite effective in producing more qualified and competent school librarian candidates who can be appointed as school librarian heads. However, this research still has some limitations due to inadequate facilities and infrastructure. Thus, there is an obstacle in the implementation of the training for prospective school library principals. Therefore, of course, this research still has a research gap that can still be filled for further research.